Analysis the ability of Alphitobius diaperinus larvae as biodegradator of potato peel waste - Diennurrahma, Aufa; Widiyaningrum, Priyantini; Indriyanti, Dyah Rini; Ngabekti, Sri (Biogenesis: Jurnal Ilmiah Biologi, 2024)
The larvae of Alphitobius diaperinus (lesser mealworms) are often regarded as pests in livestock farms; however, they possess significant potential as waste biodegraders due to their chewing mouthparts, strong jaws, and symbiotic microbes in their digestive tracts. This study investigates their ability to biodegrade potato peel waste. A Completely Randomized Design (CRD) was employed with three treatment groups: P0 (50 grams of pollard), P1 (50 grams of pollard plus 35 grams of fresh potato peel waste), and P2 (50 grams of pollard plus 5 grams of dried potato peel waste). Third instar larvae were selected based on uniform size, color, and weight. The experiment was conducted over 10 weeks, with weekly monitoring of larval development. The results indicated that A. diaperinus larvae effectively biodegraded potato peel waste, with the highest waste reduction and Waste Reduction Index (WRI) observed in the P1 group. Quantitative data showed that the WRI for P1 (8.87%) was significantly higher than that of P2 (2.94%). Biomass production was analyzed using the non-parametric Kruskal-Wallis test, revealing significant differences between groups P0 and P1, while no significant differences were found between P0 and P2 or between P1 and P2. In conclusion, A. diaperinus larvae demonstrate considerable potential as biodegraders of potato peel waste. Moreover, the combination of potato peel and pollard as a rearing substrate positively influences larval biomass production.